Exposure to Muslims in Media and Support for Public Policies Harming Muslims. (August 2017) - Saleem, Muniba; Prot, Sara; Anderson, Craig A.; Lemieux, Anthony F.
Few studies have empirically examined how media stereotypes of Muslims influence Americans' support for public policies exclusively harming Muslims. Across three studies, we tested the short-term and long-term effects of news portraying Muslims as terrorists on Americans' support for public policies harming Muslims domestically and internationally. Study 1 revealed that exposure to news portraying Muslims as terrorists is positively associated with support for military action in Muslim countries. Study 2 revealed that exposure to news portraying Muslims as terrorists is positively associated with support for public policies that harm Muslims domestically and internationally; this effect was fully mediated by perceptions of Muslims as aggressive. Experimental results from Study 3 revealed that exposing participants to negative Muslim media footage, relative to neutral or no-video footage, increased perceptions of Muslims as aggressive, increased support for harsh civil restrictions of Muslim Americans, and increased support for military action in Muslim countries. Exposure to positive Muslim footage yielded opposite results. We discuss the importance of media in exacerbating aggressive attitudes and public policies in the context of intergroup relations.